2003
DOI: 10.1083/jcb.200310067
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of type Iγ phosphatidylinositol phosphate kinase by Src regulates an integrin–talin switch

Abstract: Engagement of integrin receptors with the extracellular matrix induces the formation of focal adhesions (FAs). Dynamic regulation of FAs is necessary for cells to polarize and migrate. Key interactions between FA scaffolding and signaling proteins are dependent on tyrosine phosphorylation. However, the precise role of tyrosine phosphorylation in FA development and maturation is poorly defined. Here, we show that phosphorylation of type Iγ phosphatidylinositol phosphate kinase (PIPKIγ661) on tyrosine 644 (Y644)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
200
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(217 citation statements)
references
References 33 publications
13
200
3
Order By: Relevance
“…PIPKIg661 is phosphorylated at tyrosine 644 within the unique tail by SFKs, although in vivo FAK functions to promote tyrosine phosphorylation of PIPKIg661 by Src (Di Paolo et al, 2002;Ling et al, 2002Ling et al, , 2003. This phosphorylation event is important for the efficient association of PIPKIg661 with talin and for localization to focal adhesions (Ling et al, 2003).…”
Section: Role Of Pipkic661mentioning
confidence: 99%
See 1 more Smart Citation
“…PIPKIg661 is phosphorylated at tyrosine 644 within the unique tail by SFKs, although in vivo FAK functions to promote tyrosine phosphorylation of PIPKIg661 by Src (Di Paolo et al, 2002;Ling et al, 2002Ling et al, , 2003. This phosphorylation event is important for the efficient association of PIPKIg661 with talin and for localization to focal adhesions (Ling et al, 2003).…”
Section: Role Of Pipkic661mentioning
confidence: 99%
“…PIPKIg661 is phosphorylated at tyrosine 644 within the unique tail by SFKs, although in vivo FAK functions to promote tyrosine phosphorylation of PIPKIg661 by Src (Di Paolo et al, 2002;Ling et al, 2002Ling et al, , 2003. This phosphorylation event is important for the efficient association of PIPKIg661 with talin and for localization to focal adhesions (Ling et al, 2003). Phosphatidyl inositol 4,5-bisphosphate (PIP 2 ), which is the product generated by phosphorylation of PIP by PIP kinases, regulates the interactions between a number of cytoskeletal proteins, including the association of talin with the cytoplasmic domains of the integrin b subunits and the binding of vinculin to talin (Nayal et al, 2004).…”
Section: Role Of Pipkic661mentioning
confidence: 99%
“…To assess whether talin binding was sufficient for trans-dominant inhibition, we examined the effect of cellular expression of PIPKI␥-90, a talin-binding splice variant of PIPKI␥ (41, 49), on integrin activation. PIPKI␥-90 binds to talin at a site within the F3 subdomain of talin (41) that overlaps with the integrin-binding site (50,51). Furthermore, PIPKI␥-90 can compete with integrin ␤ tails for binding to talin (50,51).…”
Section: Expression Of Talin-binding Variants Of Pipki␥ Inhibits Intementioning
confidence: 99%
“…PIPKI␥-90 binds to talin at a site within the F3 subdomain of talin (41) that overlaps with the integrin-binding site (50,51). Furthermore, PIPKI␥-90 can compete with integrin ␤ tails for binding to talin (50,51). To test the hypothesis that competition for talin would lead to trans-dominant inhibition, the effect of GFP fusions of the talin-binding splice variant, PIPKI␥-90, and the non-binding variant, PIPKI␥-87, on integrin activation were assessed by flow cytometry.…”
Section: Expression Of Talin-binding Variants Of Pipki␥ Inhibits Intementioning
confidence: 99%
“…Equally important is understand whether signals initiated by binding of apoptotic cells alter the ability of talin to bind the β5 cytoplasmic tail. This could be at the level of either talin or a sequencespecific motif in the β5 cytoplasmic tail, and maybe tiggered by post-translational modifications [41], competition by intracellular signaling molecules [41], or by activation of a specific GTPase such as Rac1 or RhoG [16]. We have shown that αvβ5 integrin is part of a signaling pathway with the Mertk, which culminates in the association of tyrosine phosphorylated FAK with the β5 cytoplasmic tail [35].…”
Section: Discussionmentioning
confidence: 91%